The Role of Islamic Religious Education on the Development Youths’ Attitudes - Nurul Dwi Tsoraya; Okeh Primalaini; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Islamic Religious Education is something learning with giving Theory about Islam as belief, understanding, appreciation, and practice of Islamic teachings in life sourced daily to the Qur'an and hadith. Teenager is a time of transition from the age child Becomes mature. In Islam, youth are often called puberty baligh. During this time, someone has been required for performing obligatory worship and avoid His prohibitions. For that Theory, Islamic religious education is the only one Theory very appropriate and instrumental education important in shaping Act behavior and personality child teenagers and for help teenagers in overcome problems in life, and the role of family, school, and community are very important in building Act behavior of teenagers.